Pengaruh Panjang Serat Batang Labu Kuning (Cucurbita moschata) Pada Material Komposit Terhadap Sifat Tarik Bermatriks Polyester - Adam Fatkhur Rohman Hidayat (Universitas Negeri Malang, 2026)
The development of natural fiber-reinforced composite materials has increased significantly due to the demand for lightweight, environmentally friendly, and sustainable materials. One agricultural waste with potential as a composite reinforcement is pumpkin stem fiber (Cucurbita moschata). However, studies investigating the effect of pumpkin stem fiber length on the tensile properties of composites are still limited. This study aims to analyze the effect of fiber length variation on the tensile strength, strain, and modulus of elasticity of polyester matrix composites reinforced with pumpkin stem fibers. An experimental method was employed, and composite specimens were fabricated using the hand lay-up technique. Fiber length variations of 6 mm, 8 mm, 10 mm, and 12 mm were used with a volume fraction composition of 10% fiber and 90% polyester resin. Tensile testing was conducted according to ASTM D638 standards using five specimens for each fiber length variation. The evaluated parameters included tensile strength, strain, and modulus of elasticity. The results indicated that fiber length variation significantly influenced the tensile properties of the composites. The highest tensile strength was obtained at a fiber length of 12 mm with a value of 19.83 MPa, while the lowest value was recorded at 8 mm with 10.28 MPa. The highest strain value was also achieved at 12 mm with 1.6%, whereas the lowest strain value was 1.0% at 8 mm. The highest modulus of elasticity was obtained at 6 mm with a value of 1175.634 MPa, while the lowest value was observed at 10 mm with 860.167 MPa. Overall, the 12 mm fiber length exhibited the best tensile performance due to its ability to improve load transfer efficiency between the fiber and polyester matrix.